2022
DOI: 10.1001/jamaneurol.2022.3392
|View full text |Cite
|
Sign up to set email alerts
|

Association of Donanemab Treatment With Exploratory Plasma Biomarkers in Early Symptomatic Alzheimer Disease

Abstract: ImportancePlasma biomarkers of Alzheimer disease may be useful as minimally invasive pharmacodynamic measures of treatment outcomes.ObjectiveTo analyze the association of donanemab treatment with plasma biomarkers associated with Alzheimer disease.Design, Setting, and ParticipantsTRAILBLAZER-ALZ was a randomized, double-blind, placebo-controlled clinical trial conducted from December 18, 2017, to December 4, 2020, across 56 sites in the US and Canada. Exploratory biomarkers were prespecified with the post hoc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 41 publications
9
81
0
Order By: Relevance
“…This difference in the longitudinal correlations for brain and plasma amyloid is likely due to the different time windows in which these two measures are dynamic, with plasma amyloid exhibiting changes decades prior to brain amyloid. Our findings agree with the plasma biomarker findings from the TRAILBLAZER-ALZ clinical trial, where longitudinal change in brain amyloid correlated with change in plasma GFAP but not Aβ 42 /Aβ 40 [36].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This difference in the longitudinal correlations for brain and plasma amyloid is likely due to the different time windows in which these two measures are dynamic, with plasma amyloid exhibiting changes decades prior to brain amyloid. Our findings agree with the plasma biomarker findings from the TRAILBLAZER-ALZ clinical trial, where longitudinal change in brain amyloid correlated with change in plasma GFAP but not Aβ 42 /Aβ 40 [36].…”
Section: Discussionsupporting
confidence: 90%
“…Rates of change were highly correlated between p-tau181/Aβ ସଶ and p-tau231/Aβ ସଶ , and between GFAP and NfL. Our findings agree with the plasma biomarker findings from the TRAILBLAZER-ALZ clinical trial, where longitudinal change in brain amyloid was correlated with change in plasma GFAP but not Aβ ସଶ /Aβ ସ [36].…”
Section: Temporal Order Of Changes In Plasma Biomarkers and Brain Amy...supporting
confidence: 89%
See 1 more Smart Citation
“…This finding is not in line with the common idea that plasma p-tau biomarkers are more closely associated with early markers of AD such as amyloid 1,6,9 , while tau-PET is more closely associated with downstream markers of disease progression such as cognitive decline and brain atrophy 37 , as discussed in the previous paragraph. Consistent with our data, an independent study of amyloid-positive patients found that p-tau217-to-tau-PET association was stronger than p-tau217-to-amyloid-PET 38 . Furthermore, it has been shown that associations between plasma p-tau217 and PET markers evolve over the course of the disease 5 : plasma p-tau217 is associated with amyloid-PET in the earliest stages of AD, when tau burden is restricted to the medial temporal lobe.…”
Section: Discussionsupporting
confidence: 92%
“…If such a relationship can be established in clinical trials, future trials targeting early-stage AD might incorporate plasma p-tau217 as a potential surrogate endpoint 2 . Importantly, a recent clinical trial evaluating donanemab, an immunotherapy efficiently removing Aβ aggregates from the brain, has shown 23% reduction in levels of plasma p-tau217 within 6-18 months of treatment when the placebo group continued to increase 32 .…”
Section: Articlementioning
confidence: 99%